The influence of local wisdom-based gamification on students' literacy and numeracy in mathematics learning - Harina Handaryani; Hamsu Abdul Gani; Awaluddin Muin (Universitas Papua, 2026)
Literacy and numeracy are essential skills for student preparation in further education, enabling understanding, analysis of information, and problem-solving. They are critical indicators of student success and provide a foundation for future challenges. This study aims to examine the effect of local wisdom-based gamification on students' literacy and numeracy skills in mathematics learning. This study used an experimental design, namely a one-group pretest-posttest. The sample of this study was 30 seventh-grade students. The instruments in this study consisted of two types, namely a questionnaire to measure literacy skills and a test to measure numeracy skills. The pretest-posttest difference test used a paired t-test. The local wisdom-based gamification media developed was validated by material experts with an average of 85.56%, and media and design experts with an average of 93.58%, indicating the media is valid for use. These findings indicate that local wisdom-based gamification has a positive influence on improving student literacy, which is indicated by a shift in some students from the moderate category to the high category after the intervention was given (sig. = 0.001). Local wisdom-based gamification was also able to positively improve students' numeracy skills, marked by a shift in students from the low and moderate categories to the higher categories (sig. = 0.001). Thus, the implementation of local wisdom-based gamification was proven to have a significant impact on improving students' literacy and numeracy skills.